Developed empathetic capacities as a prerequisite for quality interpersonal relationships within a school environment - Биљана Масловарић; Маријана Блечић; Шај Коен (Pedagogical society of the Republic of Srpska, 2021)
The specific issue of the quality of educational process requires a quality school environment, which can be observed at several levels: first of all, through quality interpersonal relationships, and then through quality curricula and syllabi and the ecology of the school environment (Relja, 2006). A quality school atmosphere is based not only on а humane/altruistic approach to students but also on the satisfied teacher, who is characterised by a number of positive qualities, as well as on the equally satisfied student, who cultivates positive feelings towards the authority of their teachers, towards the school itself, and towards the educational process in general. Good quality relationships between people are based on empathy, which is an ability to relate to the feelings of other people. It is via empathy that the te acher, however briefly, puts on their students' shoes and thereby feels the same emotions, which is what actually allows them to truly understand their students' feelings, actions, and problems and to respond positively to them. In doing so, they show a full understanding of their needs directed towards the well-being of students. Empathy includes both cognitive and emotional components and, therefore, in the process of empathising, knowledge and emotions interact. As most authors consider it to be a regulator of different forms of behaviour, especially within the context of altruistic behaviour (Batson, Duncan, Ackerman, Buckley, and Birch, 1981), empathy represents very important kind of motivation for altruism, given the degree of emotional unity established, which is a prerequisite for effective and sincere interaction between people and an initiator of a close understanding of another person's emotional world.